The morphological, karyological and palynological features of Vicia caeserea Boiss. & Bal. (Fabaceae) - Şahin, Ahmet; Ço?ano?lu, Dursun; Gür, Nazmi (TUBITAK, 1996)
The morphological, karyological and palynological features of Vicia caeserea Boiss. & Bal., which is an endemic taxon to Turkey, are investigated. The species is annual and herbacous with an angular and two-winged stem. It has compound leaves, and both surfaces of the leaflets and the stem are covered with simple hairs. The leaflets are dorsiventral and amphistomatic. The internal morphology of the root shows secondary growth, while the herbaceous stem has only a primary structure. There is a well-developed collenchyma at the edges and the wings of the stem. The pollen grains of this species are isopolar and tricolporate, and its shape is prolate. The ornamentation is microreticulate. The diploid chromosome number of the species is 2n = 12, and only one of the chromosomes is median, the others are submedian.
Vicia caeserea Boiss. & Bal. (Fabaceae)'nin morfolojik, karyolojik ve palinolojik özellikleri
Keywords: Chromosome; Morphology; Pollen morphology; Vicia caeserea